Blood pressure asSAuLTed by the circadian clock - Eckel-Mahan, Kristin (2010)
While Cry proteins are necessary for circadian rhythmicity, they now appear to play a seminal role in blood pressure regulation. In a recent issue of Nature Medicine Doi et al. show how the circadian clock may use Cry proteins to protect from salt-sensitive hypertension.